Rich dad's increase your financial IQ : get smarter with your money - Kiyosaki, Robert T., 1947- (Kiyosaki, Robert T., 1947- Rich dad series., 2008)
Emphasizes the importance of financial intelligence to good money management and describes how to improve financial information and increase, protect, budget, and leverage money.